Turkish Student Teachers' Early Experiences in Schools: Critical Incidents, Reflection, and a New Teacher Education Program - Dannelle D. Stevens; Serap Sarigul; Hulya Deger (Networks: An Online Journal for Teacher Research, 2002)
The primary purpose of this article is to report how Turkish student teachers identify and reflect on the "critical incidents" of schooling that they bring as they enter a new teacher education program. "Critical incidents" are descriptions of incidents in one's past that are viewed as significant in one's learning and development (see Brookfield, 1998; Obara, 1993). The secondary purpose of this article is to analyze these incidents to inform the first author's teaching and field supervision.